Reform nation: the First Step Act and the movement to end mass incarceration - Eren, Colleen P. (De Gruyter eBook-Paket Rechtswissenschaften, 2023)
How one law tells the story of America's modern criminal justice movement In late 2018, the First Step Act was signed into law by President Donald Trump just hours before a government shutdown. It was one of few major pieces of federal criminal justice reform since the 1970s to move toward reversing the incarceration frenzy that had characterized United States policy. While it did not amount to revolutionary reform, in Reform Nation, Colleen P. Eren investigates it as a symbol for the larger movement's trajectory. Its unlikely passage during a period of political polarization was testament to the power of a new constellation of advocates, stakeholders, and strange bedfellow alliances. These intriguing and complex dynamics are indicative of a longer, twenty-year shift in which the movement became nationalized and mainstreamed. Using in-depth interviews with major players in the national movement, formerly incarcerated activists, celebrities, and donors, this is the first book to turn the mirror back on the criminal justice reform movement itself-the frames used, the voices heard, the capital activated among elite participants, and the bitter controversies. This snapshot in time raises much larger questions about how our democratic processes inform criminal justice policy, and where we are going in the decades to come